MEDIA BELAJAR YANG MELIBATKAN AKTIVITAS BERMAIN DAN MEWARNAI UNTUK PENDIDIKAN KESEHATAN GIGI PADA ANAK - Valentina, Anny; Aurellia, Meysia Dewi; Natassya, Amelia; Ivanson, Kevin Matthew (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
ABSTRACT Health education is an activity with a goal to convert people to have a much healthier lifestyle, by conveying health related materials. This activity would not only be implemented on adults, but also to children. The reason being is that it prevents unhealthy behavior in an early age would be the main positive outcome. However, health education for this target audience would also have its challenges. According to a study, these forms of education should be done in the form of activities, be in an optimal learning environment to further increase the children’s potentials, and having play times to entertain the children. Playing would increase the physical, mental, intellectual, and spiritual aspects in children; as they find out more about the things they had never known before. By collaborating with the Pattimura University Health Department in Ambon, DKV Untar had done educational activities regarding dental health for elementary students in the Pattimura University campus grounds. This was conducted through playful activities and the coloring of drawings. The characters portrayed in the drawing media are designed to match the physical traits of Ambon children. Prior to the character design, the data gathered showed that the children in Ambon had a dark skin tone, curly hair, larger skeletal structures, and a strong physique. Having characters who have similar physical traits as the children is important, as they could relate themselves and reduce the physical difference gap. When using this drawing media in the activity, the children had fun during coloring, so this proves that they had enjoyed this activity. By utilizing a study platform that involves playful activities and coloring characters that resemble themselves, this could be an alternative strategy to educate health towards children. ABSTRACT Health education is an activity with a goal to convert people to have a much healthier lifestyle, by conveying health related materials. This activity would not only be implemented on adults, but also to children. The reason being is that it prevents unhealthy behavior in an early age would be the main positive outcome. However, health education for this target audience would also have its challenges. According to a study, these forms of education should be done in the form of activities, be in an optimal learning environment to further increase the children’s potentials, and having play times to entertain the children. Playing would increase the physical, mental, intellectual, and spiritual aspects in children; as they find out more about the things they had never known before. By collaborating with the Pattimura University Health Department in Ambon, DKV Untar had done educational activities regarding dental health for elementary students in the Pattimura University campus grounds. This was conducted through playful activities and the coloring of drawings. The characters portrayed in the drawing media are designed to match the physical traits of Ambon children. Prior to the character design, the data gathered showed that the children in Ambon had a dark skin tone, curly hair, larger skeletal structures, and a strong physique. Having characters who have similar physical traits as the children is important, as they could relate themselves and reduce the physical difference gap. When using this drawing media in the activity, the children had fun during coloring, so this proves that they had enjoyed this activity. By utilizing a study platform that involves playful activities and coloring characters that resemble themselves, this could be an alternative strategy to educate health towards children.